The digital marketing skills gap: Developing a Digital Marketer Model for the communication industries - Royle, Jo; Laing, Audrey (International journal of information management, 2014)
•We explore digital marketing skills gaps in the communication industry.•We find digital marketing skills gaps across the communication industry.•The industry needs best practice guidance.•Blending digital skills with current marketing approaches is a key strategic challenge.•We construct a Digital Marketer Model summarising core skills. Scholarly literature suggests digital marketing skills gaps in industry, but these skills gaps are not clearly identified. The research aims to specify any digital marketing skills gaps encountered by professionals working in communication industries. In-depth interviews were undertaken with 20 communication industry professionals. A focus group followed, testing the rigour of the data. We find that a lack of specific technical skills; a need for best practice guidance on evaluation metrics, and a lack of intelligent futureproofing for dynamic technological change and development are skills gaps currently challenging the communication industry. However, the challenge of integrating digital marketing approaches with established marketing practice emerges as the key skills gap. Emerging from the key findings, a Digital Marketer Model was developed, highlighting the key competencies and skills needed by an excellent digital marketer. The research concludes that guidance on best practice, focusing upon evaluation metrics, futureproofing and strategic integration, needs to be developed for the communication industry. The Digital Marketing Model should be subject to further testing in industry and academia. Suggestions for further research are discussed.